P114 Sensitivity and cost-effectiveness of trichomonas vaginalis naat (nucleic acid amplification) assay in symptomatic female patients attending a genitourinary medicine clinic. (8th June 2017) - Swaris, Beruwalage; Partridge, David; Dewsnap, Claire; Taylor, Cheryl; Sahib, Sura
Abstract : Introduction: Trichomonas vaginalis is the commonest curable sexually transmitted infection worldwide. Diagnosis is by detecting Trichomonas organisms or its DNA. Sensitivity of microscopy in females is 45–60%. Culture has a higher sensitivity than microscopy but molecular detection offers the highest sensitivity and is considered gold standard. We currently use only microscopy and this may lead to false negatives. This study assesses sensitivity and cost-effectiveness of TV NAAT assay compared with microscopy and acridine orange (AO) staining in symptomatic female patients. Methods: Prospective study looking at symptomatic female patients attending sexual health clinic during the period from 05/10/2015 to 17/05/2016.Female patients with one or more of the following symptoms; vulval soreness, itchiness, ulceration or abnormal discharge were included. Wet microscopy was performed and dried slide was sent to the lab for AO staining. TV NAAT was added to the Chlamydia/Gonorrhoea dual testing swab. Results: 452 patients were included. Age ranged from 14–65 years. 31, 18 and 8 patients had positive NAAT, microscopy and AO respectively. Considering NAAT as the gold standard; sensitivity, specificity, PPV and NPV of microscopy and AO was 48%, 100%, 100%, 95% and 28%, 100%, 100%, 94% respectively. 51.6% of the cases would have been missed if only the microscopy was used to diagnose TV. Discussion: Overall prevalence of TV positivity in our study population was 7.52%.Microscopy provided the advantage of rapid result but failed to identify half the positives.TV NAAT testing in carefully selected symptomatic women will be of value to provide better patient care.